Manajemen Program Sosiopreneur Berbasis Pesantren dalam Mewujudkan Kemandirian Lulusan - Solechan; Beny Sintasari; Ismawati (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2026)
This study aims to analyse the management of a pesantren-based social entrepreneurship programme in an effort to strengthen the economic independence of graduates from the Fathul Ulum Islamic Boarding School in Diwek, Jombang. The study employs a qualitative approach using a case study design. Data were collected through in-depth interviews with the boarding school’s supervisors, programme managers and alumni, and supplemented by observation and documentation. Data analysis was carried out through data condensation, data presentation and drawing of conclusions. The research findings indicate that the social entrepreneurship programme is managed through integrated management functions, comprising planning, implementation and evaluation. During the planning stage, the interests and potential of the students were mapped out, forming the basis for phased development through the ‘santripreneur’, ‘pesantrenpreneur’ and ‘alumni social entrepreneur’ schemes. The programme is implemented through the involvement of students in the boarding school’s business units, as well as by providing alumni with access to capital, land, mentoring and business networks through a syirkah agreement. Evaluation is carried out on an ongoing basis through alumni forums, business mentoring and spiritual guidance. These findings indicate that alumni who participated in the programme have been able to develop independent businesses in the fields of agriculture, livestock farming, screen printing, the food industry and printing. The alumni’s economic independence is demonstrated by their ability to generate their own sources of income and manage their businesses sustainably. This research proposes a pesantren-based socio-entrepreneurial management model that integrates economic empowerment, entrepreneurship education and the values of da’wah into a single, sustainable system.